Effects of Stratified Vitamin D Supplementation in Middle-Aged and Elderly Individuals with Vitamin D Insufficiency - Lu, Yanhui; Fu, Xiaomin; Zhang, Lili; Liu, Minyan; Cheng, Xiaoling; Yan, Shuangtong; Li, Nan; Miao, Xinyu; Sun, Banruo; Li, Chunlin (Hormone and Metabolic Research, 2018)
The incidence of vitamin D deficiency is high globally, and vitamin D supplementation draws particular attention. The objective of this study was to investigate the effects of stratified vitamin D supplementation in middle-aged and elderly individuals with vitamin D insufficiency in Beijing. A total of 448 subjects aged over 40 years old were selected from a community in Beijing. Among them, 100 middle-aged and elderly people with vitamin D insufficiency were randomly selected on a voluntary basis. They were further divided into control group and intervention group. The control group received health education and lifestyle guidance, and the intervention group received lifestyle guidance and vitamin D supplementation for nine months. The doses were stratified as follows: for vitamin D insufficiency, oral vitamin D3 supplement was given at 5000 IU/w; for mild vitamin D deficiency, oral vitamin D3 supplement was given at 10 000 IU/w; for severe vitamin D deficiency, oral vitamin D3 supplement was given at 15 000 IU/w. Safety evaluation was conducted after three-month treatment. The intervention group consisted of 8%, 62%, and 30% of cases who had vitamin D insufficiency, mild vitamin D deficiency, and severe vitamin D deficiency, respectively, which were similar with the control group. It showed that the blood 25(OH)D level increased significantly in the intervention group, from 14.30±4.30 ng/ml to 33.62±6.99 ng/ml (p<0.001), in contrast to insignificant change in the control group. Stratified vitamin D supplementation effectively increased the blood 25(OH)D level, as well as the number of cases with corrected vitamin D insufficiency or deficiency.
Keywords: middle-aged and elderly people; stratified vitamin D supplementation; vitamin D insufficiency; safety; effect